2015
DOI: 10.2169/internalmedicine.54.4255
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Benign Pneumatosis Intestinalis with Portal Venous Gas and Pneumoperitoneum Induced by Acarbose

Abstract: Alpha glucosidase inhibitors have been shown to be associated with pneumatosis intestinalis (PI) in recent reports. We herein report the case of a 73-year old man who received treatment with an alpha glucosidase inhibitor (acarbose) and presented with acute abdomen. A computed tomography scan demonstrated PI in addition to intrahepatic portal air and pneumoperitoneum. During exploratory laparotomy, we found no evidence of hollow organ perforation or bowel necrosis. The patient recovered after conservative trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Three main theories have been proposed for the pathogenesis of this condition. (6) The mechanical theory postulates that the condition develops as a result of increased intraluminal pressure which allows gas to infiltrate the bowel wall via mucosal defects. In contrast, the bacterial theory postulates that PI occurs when the submucosal localization of fermenting bacteria ( e.g ., Clostridium difficile and Escherichia coli ) leads to the production of gas that subsequently accumulates in the submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Three main theories have been proposed for the pathogenesis of this condition. (6) The mechanical theory postulates that the condition develops as a result of increased intraluminal pressure which allows gas to infiltrate the bowel wall via mucosal defects. In contrast, the bacterial theory postulates that PI occurs when the submucosal localization of fermenting bacteria ( e.g ., Clostridium difficile and Escherichia coli ) leads to the production of gas that subsequently accumulates in the submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Otros nombres conocidos para esta entidad son linfoneumatosis quística, linfoneumatosis peritoneal, enfisema quístico y enfisema bulloso del intestino. Para la explicación de esta entidad existen varias teorías propuestas (2,4,7,9): la teoría mecánica sugiere que el gas se origina en la luz intestinal y se produce una disección de la pared por aumento de la presión (2,4,8); en otros casos se cree que ocurren por alteración inmune (3), medicamentos o procedimientos (9). La segunda teoría se basa en una ruptura de los alvéolos a nivel pulmonar, en el que el gas llega a la pared intestinal por el retroperitoneo y mesenterio (3,4,8,9), y la tercera teoría plantea que hay bacilos productores de gas en la submucosa de la pared intestinal (2,4,8,9).…”
Section: Neumatosis Quística Intestinalunclassified
“…Residente de Radiología de la Universidad CES. 4. Residente de Radiología de la Universidad Pontificia Bolivariana -Cedimed.…”
unclassified
See 1 more Smart Citation
“…A study that compared the CT findings in patients with benign or life-threatening PI showed that certain CT features, including mesenteric stranding, bowel wall thickening, and ascites, were present in more than 90% of patients with severe PI and correlated significantly with life-threatening disease [7]. Similarly, the presence of hepatoportal or portomesenteric venous gas and a linear pattern of intramural gas may predict a deleterious outcome, associated with intestinal infarction [68], but portal venous gas or pneumoperitoneum has been seen in a patient with benign PI [9]. In our patients, both case 1 and case 2, no obvious findings suggesting portal venous gas or pneumoperitoneum were observed.…”
Section: Case Presentationmentioning
confidence: 99%